2012
DOI: 10.1007/s11284-012-0956-2
|View full text |Cite
|
Sign up to set email alerts
|

Implications of seasonal variation in nitrate export from forested ecosystems: a review from the hydrological perspective of ecosystem dynamics

Abstract: In recent decades, the seasonal variation in NO3− discharge from forest ecosystems has been used increasingly by ecologists and hydrologists as a diagnostic indicator of the nutrient status of ecosystems. Major factors underlying the seasonal patterns of stream NO3− concentration include seasonal variations in (1) ecosystem nutrient demand, (2) solute transport capability of the hydrological condition, and (3) in‐stream nutrient usage and supply. In this article I show how case studies have helped elucidate th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 67 publications
0
24
0
Order By: Relevance
“…Cirmo and McDonnell [] speculated that increased litter decomposition at the end of the growing season would create a significant dissolved inorganic N pool in soil waters, though such concentration increases were not observed during and after autumn leaf fall in a Vermont forest [ Sebestyen et al ., ]. Subsequent hydrologic flushing from that nitrification source during the dormant season may result in elevated stream nitrate concentrations [ Ohte , ] but not necessarily increased proportions of unprocessed atmospheric nitrate. However, Sebestyen et al .…”
Section: Major Drivers Influencing Atmospheric Nitrate Transport In Cmentioning
confidence: 96%
“…Cirmo and McDonnell [] speculated that increased litter decomposition at the end of the growing season would create a significant dissolved inorganic N pool in soil waters, though such concentration increases were not observed during and after autumn leaf fall in a Vermont forest [ Sebestyen et al ., ]. Subsequent hydrologic flushing from that nitrification source during the dormant season may result in elevated stream nitrate concentrations [ Ohte , ] but not necessarily increased proportions of unprocessed atmospheric nitrate. However, Sebestyen et al .…”
Section: Major Drivers Influencing Atmospheric Nitrate Transport In Cmentioning
confidence: 96%
“…The change in both the source of N, from surface to deep soils, and the role of hydrologic connectivity between the soils and the stream is suggested by the altered relationship between export and discharge (Figure 3). Stoddard (1994) and Ohte (2012) suggested that seasonality of stream DIN concentration and export is an important diagnostic indicator of watershed nitrogen dynamics. Before clearcutting, WS 7 had a pattern of winter low and summer high DIN concentrations similar to reference watersheds at Coweeta, but we found very clear changes in DIN seasonality as a result of clearcutting WS 7.…”
Section: Effect Of Clearcutting On Din Exportmentioning
confidence: 99%
“…For example, summer maximum nitrate concentrations have been observed in Japan (Mitchell and others 1997;Ohte and others 2001;Ohte 2012), Baltimore, MD (Tague and Band 2004), the Upper Susquehanna River basin in New York (Goodale and others 2009), eastern Tennessee (Lutz and others 2012), and western North Carolina at Coweeta Hydrologic Laboratory (Swank and Vose 1997;Worrall and others 2003). This summer peak has generally been attributed to high soil microbial nitrification under conditions of adequate soil water availability and warm soil temperatures during the growing season (Knoepp and Swank 1998;Goodale and others 2009;Brookshire and others 2011;Ohte 2012). Band and others (2001) suggested that this accumulated nitrate could then be flushed from riparian zones during summer, a time when there is also little overland flow to dilute streamwater concentrations.…”
Section: Introductionmentioning
confidence: 99%
“…8 shows the change in concentration over distance for NO 3 -N. The concentration of NO 3 -N decreased over both intervals, but the decrease over the e-d interval on the upstream side was greater than the decrease over the b-a interval on the downstream side. Furthermore, the decrease in concentration was greater during the summer season when the air temperature is high [7,8]. Fig.…”
Section: Factors Impacting Water Quality Of a Small Stream In A Mountainmentioning
confidence: 85%